UI design revamp of Dewan Filharmonik Petronas (DFP) online payment web pages - positive or negative emotion? / Muhammad Hariz Hasnan ... [et al.] - Hasnan, Muhammad Hariz; Loh, Wai Xin; Lau, Chewvy; Ling, Qian Ping; Wong, Si Ying (Universiti Teknologi MARA, Kedah, 2023)
Online payment methods allow users to conduct transactions and payment. Nowadays, online payment methods are widely used for any type of business, including the sale of tickets for live performing arts. The Dewan Filharmonik Petronas (DFP) is Malaysia's first concert venue dedicated to classical music, jazz, and world music genres concerts, with tickets available for purchase by the public via their website. However, the DFP website has a problem with online payments in that when a user wants to buy an online ticket, they are directed to another website called MPO via the link www.mpo.com.my. The DFP's website only provides live performance event information, no transaction activity is available on the website. The revamping of UI design in this website was done to optimize the online transaction pages. This qualitative study is to capture the user emotion on the revamped UI design of DFP online purchase pages. Six participants with IT literacy and experience purchasing online tickets at the novice, beginner, and expert levels were interviewed for this study. The instrument to measure user emotion is Premo. It is a non-verbal self-report tool, which has 14 different emotions with hand drawn characters, seven of which are positive and the other seven are negative emotions. The interview session was done in the following manner: the researchers began by asking demographic questions, followed by openended questions. Then, show the participants the revamped online transactions UI design and ask them to choose one or more emotions from the Premo hand-drawn characters based on their feelings after seeing the UI design. In conclusion, four participants chose positive emotions and two chose negative emotions. This demonstrates that the revamped website UI design is seen as a positive design.